2020
DOI: 10.1016/j.bja.2019.12.019
|View full text |Cite
|
Sign up to set email alerts
|

A randomised double-blind dose–response study of weight-adjusted infusions of norepinephrine for preventing hypotension during combined spinal–epidural anaesthesia for Caesarean delivery

Abstract: Background: Norepinephrine infusion has been suggested as an effective method for preventing hypotension during spinal anaesthesia for Caesarean delivery. However, optimal dosing regimens for norepinephrine have not been well established. This study aimed to determine the doseeresponse characteristics of a weight-adjusted fixed-rate infusion of norepinephrine to prevent hypotension during neuraxial anaesthesia for Caesarean delivery. Methods: In a double-blind, randomised controlled trial, 80 parturients havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
47
5
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 19 publications
4
47
5
3
Order By: Relevance
“…The ED50, ED85, and ED95 values for a prophylactic dose of norepinephrine were 0.029 (95% CI 0.008–0.042), 0.068 (95% CI 0.055–0.099), and 0.105 (95% CI 0.082–0.172) µg/kg/min, respectively. A loading bolus of 6 μg norepinephrine was given before norepinephrine infusion, and only bupivacaine was administrated for spinal anesthesia in our study; however, we found similar results, though different prophylactic doses were employed by Wei et al 13 The prophylactic doses of norepinephrine employed in our study was in accordance with Hasanin et al 7 and Fu et al 12 Significantly, the work reported by Hasanin et al 7 provided us a good foundation without exploring the ED50 and ED90 values. In addition, we further explored the overall stability of SBP control versus baseline, including MDPE and MDAPE.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The ED50, ED85, and ED95 values for a prophylactic dose of norepinephrine were 0.029 (95% CI 0.008–0.042), 0.068 (95% CI 0.055–0.099), and 0.105 (95% CI 0.082–0.172) µg/kg/min, respectively. A loading bolus of 6 μg norepinephrine was given before norepinephrine infusion, and only bupivacaine was administrated for spinal anesthesia in our study; however, we found similar results, though different prophylactic doses were employed by Wei et al 13 The prophylactic doses of norepinephrine employed in our study was in accordance with Hasanin et al 7 and Fu et al 12 Significantly, the work reported by Hasanin et al 7 provided us a good foundation without exploring the ED50 and ED90 values. In addition, we further explored the overall stability of SBP control versus baseline, including MDPE and MDAPE.…”
Section: Discussionsupporting
confidence: 80%
“…In clinical practice, norepinephrine has proven efficacy and safety as a prophylactic vasopressor drug infusion for obstetric anesthesia. Adverse outcomes, such as reactive hypertension and bradycardia, have a low probability of occurrence 12,13 . Onwochei et al 8 carried out a sequential allocation dose‐finding study and demonstrated that the ED90 of intermittent boluses of norepinephrine to prevent postspinal anesthesia hypotension was 5.8 μg (95% CI: 5.01–6.59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kg − 1 .min − 1 [12] and 0.08 mcg. Kg − 1 .min − 1 [18]); however, these studies were not available when we started our study.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Norepinephrine has been used to treat intraoperative hypotension, and its use has been studied extensively. [5][6][7] Norepinephrine regulates blood pressure and heart rate via activation of aand b-adrenergic receptors. However, norepinephrine has well-known side effects, such as increased myocardial oxygen consumption and arrhythmias, which may ultimately worsen prognosis despite positive hemodynamic effects.…”
mentioning
confidence: 99%